Regulation of Axon Formation by Clonal Lines of a Neural Tumor - Seeds, N. W. (1970)
Clonal lines of neuroblastoma cells were found to extend or retract axons depending upon the concentration of serum. Neurite extension was not inhibited by cycloheximide but was sensitive to colchicine or vinblastine, suggesting that neurite formation is dependent upon the assembly of microtubules or neurofilaments from preformed protein subunits.